2015
DOI: 10.1109/tuffc.2015.007353
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between shear wave dispersion magneto motive ultrasound and transient elastography for measuring tissue-mimicking phantom viscoelasticity

Abstract: Several methods have been developed over the last several years to analyze the mechanical properties of soft tissue. Elastography, for example, was proposed to evaluate soft tissue stiffness in an attempt to reduce the need for invasive procedures, such as breast biopsies; however, its qualitative nature and the fact that it is operator-dependent have proven to be limitations of the technique. Quantitative shearwave- based techniques have been proposed to obtain information about tissue stiffness independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
1
25
0
1
Order By: Relevance
“…The depth of acquisition (30 mm to 90 mm) of the default used preset here is adequate for most applications, including phantom and pre-clinical studies (Almeida et al, 2015;Colello Bruno et al, 2014). Here, the depth is limited to 30 mm because a minimal propagation path of 10 mm is necessary to estimate the attenuation and velocity of the shear wave by using Equations 2, 3, and 4 (Deffieux et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The depth of acquisition (30 mm to 90 mm) of the default used preset here is adequate for most applications, including phantom and pre-clinical studies (Almeida et al, 2015;Colello Bruno et al, 2014). Here, the depth is limited to 30 mm because a minimal propagation path of 10 mm is necessary to estimate the attenuation and velocity of the shear wave by using Equations 2, 3, and 4 (Deffieux et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a single-cycle configuration, tracking the ultrasound for a T US = 50 ms is sufficient to analyze MMUS and SDMMUS. Furthermore, the multiple reflections of the shear wave (which occur in the phantom walls) decrease and the overall acquisition time diminishes as compared to harmonic excitation (Almeida et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge and based on literature review [20][21][22][23], the Kelvin Voigt showed more satisfactory results for viscoelastic materials than the others and it will be use in this thesis for evaluating the viscoelastic parameters. Therefore, we will only discuss the Voigt Model.…”
Section: Viscoelasticitymentioning
confidence: 96%